Pengaruh Fasilitas Kerja dan Efektivitas Komunikasi Terhadap Produktivitas Kerja Karyawan Phone Verification di PT Swakarya Insan Mandiri Kota Bekasi - Vanessa Ayu Lestari; Dinni Agustin; Ahmadun Ahmadun (JURNAL ADMINISTRASI & MANAJEMEN, 2025)
ABSTRACT This study aims to examine the influence of Work Facilities and Communication Effectiveness on Employee Productivity in the Phone Verification division at PT Swakarya Insan Mandiri, Bekasi. The research is motivated by the phenomenon of declining productivity, which is often associated with complaints about work equipment and communication barriers in the workplace. The research method employed is a quantitative approach with an associative research design. Data were collected through questionnaires distributed to 50 respondents and analyzed using Structural Equation Modeling (SEM) with the Partial Least Square (PLS) approach, utilizing SmartPLS 4 software. The results show that Work Facilities have no significant effect on Work Productivity, while Communication Effectiveness has a significant and positive influence on Work Productivity. Simultaneously, both independent variables strongly influence Work Productivity. These findings highlight the essential role of effective communication in enhancing employee performance, particularly in work environments that demand coordination and accuracy such as the Phone Verification division. Keywords: Work Facilities, Communication Effectiveness, Work Productivity, SEM, SmartPLS.